Reliability of balance evaluation using a KAT2000 and a kistler force plate - Wei-Hsiu Lin; Lee, A. J. Y.; Huang, C. H. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Balance is the process of maintaining the center of gravity (COG) within the body`s base of support. Previous studies used several different methods to examine the relationships between balance control, injury probability and the efficiency of rehabilitation after injury. However, very few studies investigated the reliability of the balance measuring equipment. The purpose of this study was to examine the reliability of two balance evaluation instruments. Methods Nineteen healthy physicaly active college students were recruited. They were randomly assigned and counter balanced to undertake the Kistler force plate balance test (open and closed eyes with left or right leg upright standing) and the KAT2000 static and dynamic balance test (left or right leg and the bilateral standing test). All the balance tests were repeated after ten days again. Repeated measures t-test, Pearson correlation and the Intra-class correlation coefficients (ICC) were used to determine the reliability of each balance test performance. Results There were strong correlations between LS, BS and BD (0.67, 0.71 & 0.76) in the KAT2000 balance test. The t-test indicated that there were significant differences in RS and BD pre- and post-test. The ICC also indicated that BS and BD had normal to good reliability (0.73 & 0.80). There were strong correlations between OL, OR and CL in the Kistler balance test. The t-test indicated that no significant difference in any pre- and post-test. The ICC also indicated that all balance tests on the Kistler force plate had normal to good reliability (0.61~0.80). These results show that the limitations of different balance equipment need to be taken into the consideration. The Romberg standing test performed on the Kistler force plate has good reliability in the static (open or close eyes) balance performance test. There was poor reliability in the KAT2000 balance test, both in the left and the right static testing procedure. Balance tests using the KAT2000 might be affected by a learning effect and need further evaluation when used for static and dynamic balance performance.